1999
DOI: 10.1007/s000660050047
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Failures after Whole Abdominal Irradiation in Gastrointestinal Lympomas

Abstract: General prophylactic enclosure of the inguinal lymph nodes in the case of whole abdominal irradiation in gastrointestinal lymphoma seems to be unnecessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
7
0
3
Order By: Relevance
“…The relapse rate after these rather low radiation doses also indicates a possible dose-effect correlation. Also Reinartz et al [37] reported the importance of adequate radiation doses for local tumor control in the treatment of (exclusively) lowgrade gastrointestinal NHL.…”
Section: Radiation Dose and In-field Relapsementioning
confidence: 99%
“…The relapse rate after these rather low radiation doses also indicates a possible dose-effect correlation. Also Reinartz et al [37] reported the importance of adequate radiation doses for local tumor control in the treatment of (exclusively) lowgrade gastrointestinal NHL.…”
Section: Radiation Dose and In-field Relapsementioning
confidence: 99%
“…Since the fields are usually very large (40 cm × 30 cm or larger), most patients experience severe side effects, especially myelosuppression. Many of the randomized trials comparing WAI and chemotherapy failed to show a statistically significant difference in overall survival, mainly because of disruption of radiation treatment due to hematologic toxicity [7,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Der zeitliche Verlauf der Anzahl der Patienten im Risiko wurde in 22 dieser 45 Arbeiten (49%; 95%-Konfidenzintervall: 33 bis 65%) dokumentiert [15, 17, 19, 28, 30-32, 64, 69-71, 96, 108, 118, 131, 137, 139, 149, 156, 163, 169, 177]. In ebenfalls elf Arbeiten wurden die Ergebnisse lediglich nicht aktuarisch ("crude") ausgewertet [5,24,72,77,81,128,132,144,150,151,153]. In zwei Arbeiten [22,25] Table 2.…”
Section: Qualitätsanalyse Der Zeitschrift "Strahlentherapie Und Onkolunclassified